Comprehensive Evaluation of Energy Efficiency Based on TOPSIS for Protocols of Collaborative Wireless Sensor Networks. (5th April 2015) - Li, Ji'an; Zhou, Jianzhong; Zhang, Yongchuan
Comprehensive evaluation of energy efficiency of protocols under certain cost conditions is a relatively new and ill-defined concept for collaborative wireless sensor networks (CWSN). In this paper, multicriteria decision making (MCDM) theory is introduced into comprehensive evaluation of energy efficiency of clustering protocols, which is the predecessor of collaborative protocols. Parameters about energy efficiency of total network, including cost and benefit parameters, are selected to construct a metrics system for the comprehensive evaluation. Technique for order preference by similarity to ideal solution (TOPSIS) without criterion weight is proposed as the method of MCDM, and it can be used to select most efficient scheme among many schemes. The experimental results show that the proposed method is effective and can be used in CWSN protocol selection and deployment of nodes.